Sex-based differences in the manifestations and complications of sickle cell disease: Report from the Sickle Cell Disease Implementation Consortium. - Rita V Masese (Public Library of Science (PLoS), 2021)
Introduction Sex-based clinical outcome differences in sickle cell disease (SCD) remain largely unknown despite evidence that female sex is associated with an increased lifespan. To better characterize sex-based differences in SCD, we assessed pain, treatment characteristics, laboratory measures and complications among males and females currently enrolled in the Sickle Cell Disease Implementation Consortium (SCDIC) registry. Methods The SCDIC consists of eight comprehensive SCD centers and one data coordinating center that received funding from the National Heart Lung and Blood Institute to improve outcomes for individuals with SCD. Eligibility criteria included: 15 to 45 years of age and a confirmed diagnosis of SCD. Self-report surveys were completed and data were also abstracted from the participants' medical records. Results A total of 2,124 participants were included (mean age: 27.8 years; 56% female). The majority had hemoglobin SS SCD genotype. Females had worse reports of pain severity (mean (SD) T-score 51.6 (9.6) vs 49.3 (10), p<0.001), more vaso-occlusive episodes (p = 0.01) and a higher occurrence of 3 or more hospital admissions in the past year (30.9% vs. 25.5, p = 0.03). On multivariable analysis, males had higher odds of acute chest syndrome (odds ratio (OR) 1.4, p = 0.002), cardiovascular (OR 1.70, p<0.001) and musculoskeletal (OR 1.33, p = 0.0034) complications and lower odds of depression (OR 0.77, p = 0.0381). Females had higher fetal hemoglobin levels with and without hydroxyurea use (9.6% vs 8.5%, p = 0.03 and 3% vs 2.2%, p = 0.0005, respectively). Conclusion Our data suggests that sex differences in clinical outcomes do occur among individuals with SCD. Future research needs to explore the mechanisms underlying these differences.